Edentulism and shortened dental arch in Brazilian elderly from the National Survey of Oral Health 2003 Edentulismo dental y arco dental reducido en ancianos de la Pesquisa Nacional de Salud Bucal 2003 Edentulismo e arco dental reduzido em idosos do Inquérito Nacional de Saúde Bucal 2003 - Marco Túlio Freitas Ribeiro; Marco Aurélio Camargo da Rosa; Rosa Maria Natal de Lima; Andréa Maria Duarte Vargas; João Paulo Amaral Haddad; Efigênia Ferreira e Ferreira (Universidade de São Paulo, 2011)
OBJECTIVE: To describe the distribution of edentulism and estimate the prevalence of functional dentition and shortened dental arch among elderly population. METHODS: A population-based epidemiological study was carried out with a sample of 5,349 respondents aged 65 to 74 years obtained from the 2002 and 2003 Brazilian Ministry of Health/Division of Oral Health survey database. The following variables were studied: gender; macroregion of residence; missing teeth; percentage that met the World Health Organization goal for oral health in the age group 65 to 74 years (50% having at least 20 natural teeth); presence of shortened dental arch; number of posterior occluding pairs of teeth. The Chi-square test assessed the association between categorical variables. The Kruskal-Wallis and Mann-Whitney tests were used to assess differences of mean between number of posterior occluding pairs teeth, macro-region and gender. RESULTS: The elderly population had an average of 5.49 teeth (SD: 7.93) with a median of 0. The proportion of completely edentulous respondents was 54.7%. Complete edentulism was 18.2% in the upper arch and 1.9% in the lower arch. The World Health Organization goal was achieved in 10% of all respondents studied. However, only 2.7% had acceptable masticatory function and aesthetics (having at least shortened dental arch) and a mean number of posterior occluding pairs of 6.94 (SD=2.97). There were significant differences of the percentage of respondents that met the World Health Organization goal and presence of shortened dental arch between men and women. There were differences in shortened dental arch between macroregions. CONCLUSIONS: The Brazilian epidemiological oral health survey showed high rate of edentulism and low rate of shortened dental arch in the elderly population studied, thus suggesting significant functional and aesthetic impairment in all Brazilian macroregions especially among women. OBJETIVO: Describir la distribución de edentulismo y estimar la prevalencia de dentición funcional y arco dentario reducido en ancianos. MÉTODOS: Estudio epidemiológico poblacional con 5.349 individuos de 65 a 74 años del banco de datos de la pesquisa nacional de salud bucal del Ministerio de la Salud/Coordinación Nacional de Salud Bucal en 2002 y 2003. Se evaluaron pérdida dentaria; cumplimiento de la meta de la Organización Mundial de Salud para el grupo etario (50% con al menos 20 dientes); presencia de arco dental reducido, número de pares en oclusión posterior; sexo y macro-región de la residencia. La prueba de chi-cuadrado evaluó la asociación entre variables categóricas. Las pruebas Kruskal-Wallis y Mann-Whitney fueron usadas para determinar diferencias del número promedio de pares de dientes posteriores en oclusión, macro-región y sexo. RESULTADOS: Los ancianos tenían, en promedio, 5,49 dientes (DE= 7,93) (mediana =0). El porcentaje de individuos totalmente edéntulos fue de 54,7%. El edentulismo fue de 18,2% en el arco superior y 1,9% en el inferior. La meta de la Organización Mundial de la Salud fue alcanzada por 10% de los individuos, sin embargo, 2,7% tenían la función masticadora y estética aceptables (con al menos el arco dental reducido). Entre ellos, el número promedio de pares de oclusión posterior fue 6,94 (DE=2,97). La presencia de arco dental reducido fue más frecuente entre hombres, así como el alcance de la meta de la Organización Mundial de la Salud. También se observaron diferencias con relación al arco dental reducido entre las macro-regiones. CONCLUSIONES: El levantamiento epidemiológico de salud bucal brasileña presentó alto porcentaje de edentulismo y bajo arco dental reducido, sugiriendo el comprometimiento funcional y estético considerable en todas las regiones del país, especialmente entre mujeres. OBJETIVO: Descrever a distribuição de edentulismo e estimar a prevalência de dentição funcional e arco dentário reduzido entre idosos. MÉTODOS: Estudo epidemiológico populacional com 5.349 indivíduos de 65 a 74 anos do banco de dados do inquérito nacional de saúde bucal do Ministério da Saúde/Coordenação Nacional de Saúde Bucal em 2002 e 2003. Foram avaliados perda dentária; cumprimento à meta da Organização Mundial da Saúde para a faixa etária (50% com pelo menos 20 dentes); presença de arco dental reduzido, número de pares em oclusão posterior; sexo e macro-região da residência. O teste qui-quadrado avaliou a associação entre variáveis categóricas. Os testes Kruskal-Wallis e Mann-Whitney foram usados para determinar diferenças do número médio de pares de dentes posteriores em oclusão, macro-região e sexo. RESULTADOS: Os idosos tinham, em média, 5,49 dentes (DP = 7,93) (mediana = 0). A porcentagem de indivíduos totalmente edêntulos foi de 54,7%. O edentulismo foi de 18,2% no arco superior e 1,9% no inferior. A meta da Organização Mundial da Saúde foi alcançada por 10% dos indivíduos; no entanto, 2,7% tinham a função mastigatória e estética aceitáveis (com pelo menos o arco dental reduzido). Entre esses, o número médio de pares de oclusão posterior foi 6,94 (DP = 2,97). A presença de arco dental reduzido foi mais freqüente entre homens, assim como o alcance da meta da Organização Mundial da Saúde. Também se observaram diferenças quanto ao arco dental reduzido entre as macro-regiões. CONCLUSÕES: O levantamento epidemiológico de saúde bucal brasileira apresentou alto percentual de edentulismo e baixo de arco dental reduzido, sugerindo o comprometimento funcional e estético considerável em todas as regiões do País, especialmente entre mulheres.